Parametric study of sputtering microchannels via focused ion beam (FIB) - Mohd Shahar, Siti Fatimah; Jaafar, Israd Hakim; Ali, Mohammad Yeakub (Asian Research Publishing Network (ARPN), 2015)
Focused ion beams (FIB) are used in microfabrication and have certain advantages compared to photolithography and other micromachining technologies. The main advantage is that it can be used for direct writing/patterning of the target material. FIB can create a variety of geometric features, has the ability to process without masks, and can accommodate the patterning of a variety of materials. In high aspect micromilling, the beam current, beam diameter as well as the dwell time are some of the parameters that need to be taken into account. In this research, different beam currents with respective beam diameters were used to investigate the optimum parameters that can be achieved in milling microchannels. The target material that was used in this experiment was Silicon < 100 >. The wafer used had 250 μm thicknesses. The results observed were the channel width, gap between the channels, and the channel depth. The main trend observed was that when the beam current increases, the depth and the channels' width also increase whereas the channels' gap decreases. Defects such as side wall tapering effect and swelling were noticed from the experiments that used the unsuitable parameters because the values of beam current are not enough to sputter the silicon surface. The best beam current use that give the nearest result to the actual pattern is around 7.0-8.0 pA. Extended research need to be conducted to see the effect on the surface roughness of the channels.